Maximizing business performance and efficiency through intelligent systems - Rishi, Om Prakash, 1970-; Sharma, Anukrati, 1981- (Business Science Reference (an imprint of IGI Global, 2017)
"[This book] is an essential reference publication for the latest research on methods to use artificial intelligence in organizational settings. Featuring coverage on a broad range of topics such as information retrieval, fuzzy systems, and neural networks, this book is ideally designed for students, professionals, and researchers seeking research on emerging advances in business technology applications"- Resumé vydavatel
"Premier reference source"--Cover.
Keywords: umělá inteligence; podnikový management; inovace; artificial intelligence; industrial management; innovations; kolektivní monografie; elektronické knihy; collective monographs; electronic books